Crystal structure, spectroscopic investigations, and density functional studies of (Z)-2-(1H-imidazol-1-yl)-1-(3-methyl-3-mesitylcyclobutyl)ethanone oxime - Saracoglu, H.; Cukurovali, A. (Taylor & Francis Ltd, 2016)
The title molecule, (Z)-2-(1H-imidazol-1-yl)-1-(3-methyl-3-mesitylcyclo-butyl)ethanone oxime (C-19 H-25 N-3 O), was prepared and characterized by(1)H-Nuclear magnetic resonance (NMR), C-13-NMR, infrared spectroscopic methods, and X-ray single-crystal determination. The compound crystallizes in the orthorhombic space group P c c n with a = 31.4660(17) angstrom, b = 11.2140(7) angstrom, and c = 10.0710(8) angstrom. In addition to molecular geometry from X-ray determination, vibrational frequencies and gauge, including atomic orbital, H-1- and C-13-NMR chemical shift values of the title compound in the ground state, were calculated using the density functional method with the 6-31G(d) basis set. The calculated results show that the optimized geometries can well reproduce the crystal structure. Besides, the theoretical vibrational frequencies and chemical shift values show good agreement with experimental values. The predicted nonlinear optical properties of the title compound are greater than those of urea. Density functional theory calculations of molecular electrostatic potentials, frontier molecular orbitals, and thermodynamic properties of the title compound were carried out at the B3LYP/6-31G(d) level of theory.
Keywords: Computational chemistry; NMR spectroscopy; oximes; imidazoles; nonlinear optical properties